![\huge\underline{\red{A}\blue{n}\pink{s}\purple{w}\orange{e}\green{r} -}](https://tex.z-dn.net/?f=%5Chuge%5Cunderline%7B%5Cred%7BA%7D%5Cblue%7Bn%7D%5Cpink%7Bs%7D%5Cpurple%7Bw%7D%5Corange%7Be%7D%5Cgreen%7Br%7D%20-%7D)
- Given - <u>an </u><u>equation</u><u> </u><u>in </u><u>a </u><u>standard</u><u> </u><u>form</u>
- To do - <u>simplify</u><u> </u><u>the </u><u>equation</u><u> </u><u>so </u><u>as </u><u>to </u><u>obtain </u><u>an </u><u>easier </u><u>one</u>
<u>Since </u><u>the </u><u>equation</u><u> </u><u>provided </u><u>isn't</u><u> </u><u>i</u><u>n</u><u> </u><u>it's</u><u> </u><u>general</u><u> </u><u>form </u><u>,</u><u> </u><u>let's</u><u> </u><u>first </u><u>convert </u><u>it </u><u>~</u>
<u>General</u><u> </u><u>form </u><u>of </u><u>a </u><u>Linear</u><u> equation</u><u> </u><u>-</u>
![\bold{ax + b = 0}](https://tex.z-dn.net/?f=%5Cbold%7Bax%20%20%2B%20b%20%3D%200%7D)
<u>T</u><u>he </u><u>equation</u><u> </u><u>after </u><u>getting</u><u> </u><u>converted</u><u> </u><u>will </u><u>be </u><u>as </u><u>follows</u><u> </u><u>~</u>
![- 7 + ( \frac{4x + 2}{2} ) = 8 \\ \\ \implies \: \frac{ - 14 + 4x + 2}{2} = 8 \\ \\ \implies \: - 14 + 4x + 2 = 16 \\ \\ \implies \: 4x = 16 + 14 - 2 \\ \\ \implies \: 4x = 28 \\ \\\bold{ General \: form \: \dashrightarrow \: 4x - 28 = 0}](https://tex.z-dn.net/?f=%20-%207%20%2B%20%28%20%5Cfrac%7B4x%20%2B%202%7D%7B2%7D%20%29%20%20%3D%208%20%5C%5C%20%20%5C%5C%20%5Cimplies%20%5C%3A%20%20%5Cfrac%7B%20-%2014%20%2B%204x%20%2B%202%7D%7B2%7D%20%20%3D%208%20%5C%5C%20%20%5C%5C%20%20%5Cimplies%20%5C%3A%20%20-%2014%20%2B%204x%20%2B%202%20%3D%2016%20%5C%5C%20%20%5C%5C%20%5Cimplies%20%5C%3A%204x%20%3D%2016%20%2B%2014%20-%202%20%5C%5C%20%20%5C%5C%20%5Cimplies%20%5C%3A%204x%20%3D%2028%20%5C%5C%20%20%5C%5C%5Cbold%7B%20General%20%5C%3A%20form%20%5C%3A%20%20%5Cdashrightarrow%20%20%5C%3A%204x%20-%2028%20%3D%200%7D)
hope helpful ~
To solve for E you'll add 867 to 108.
E - 867 = 108
E = 108 + 867
E = 975
Hope this helps :)
Answer:
A= 21 m
Step-by-step explanation:
A=22/10
A=integral(a,b) [f(x)-g(x)]dx
Since the function is even (the function is mirrored over the y axis) we can evaluate the integral from 0 to 1 and then multiply our answer by 2 since we have the same area on each side of the y axis.
We get A=2*int.(0, 1)[(x^2)-(-2x^4)]dx
Now we can integrate by term.
2*[int.(0, 1)[x^2]dx+int(0, 1)[2x^4]dx]
Now factor out constants.
2*[int(0,1)[x^2]dx+2int(0,1)[x^4]dx]
Now integrate.
2*[(x^3/3)|(0,1) + 2*(x^5/5)|(0,1)]
Now solve.
2*[(1/3)+2*(1/5)]
=22/10
Hope you can decipher what I wrote!
F = 30
g = 15
Yeah, hope this helps, etc.